Planar structures with automatically generated bevel joints. (May 2018) - Su, Zhilong; Chen, Lujie; He, Xiaoyuan; Yang, Fujun; Sass, Lawrence
Highlights: Automatic finger joint generation. Rapid prototyping of seamless planar structure. Physical model made of CNC cut or 3D printed parts. Graphical abstract: Abstract: A generative method based on computer algorithms is proposed to automatically produce parts of planar structures ready for fabrication. The parts resemble surface patches of the digital model of a structure. Each part is generated with bevel joints on the edges so that part-to-part connection is enabled by friction of the joints. The shape of a bevel joint is determined by the interior angle between two parts, and is modelled by a number of parameters, including the thickness of a planar material in use. The bevel joints consist of slanted planes, and in principle when they are assembled, no gap exists on the surface of the physical structure. Due to the slanted planes, the joints cannot be fabricated by a laser cutter that can only produce vertical cuts. We experimented the fabrication with a three-axis CNC router and a 3D printer; both produced accurate and robust parts; however, there is limitation in using a CNC cutter, which is discussed in details.